2016
DOI: 10.1111/jfd.12469
|View full text |Cite
|
Sign up to set email alerts
|

Malformations of the gill filaments of the ruffe Gymnocephalus cernuus (L.) (Pisces) caused by echinostomatid metacercariae

Abstract: In parasite surveys of fishes from Lake Balaton and its tributaries in Hungary, infections with metacercariae of a species of the digenean genus Echinochasmus (Trematoda: Echinostomatidae) were found in seven species of fish. In ruffe, Gymnocephalus cernuus, malformations of the gill filaments apparently caused by these infections were observed. These malformations were in the form of bifurcations of the filaments at about their mid‐length. At the point where the filaments bifurcate, an Echinochasmus metacerca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Mature worms of this species, like other echinochasmids in the cluster, had 20 adoral spines. Unfortunately, the authors (Molnár et al ., 2016) did not provide a detailed description of morphological characteristics for cercaria but indicated that ‘the tail was almost as long as the body’. However, based on the figure in the publication, this larval stage had a tail that is characteristic of long-tailed Echinochasmidae cercariae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mature worms of this species, like other echinochasmids in the cluster, had 20 adoral spines. Unfortunately, the authors (Molnár et al ., 2016) did not provide a detailed description of morphological characteristics for cercaria but indicated that ‘the tail was almost as long as the body’. However, based on the figure in the publication, this larval stage had a tail that is characteristic of long-tailed Echinochasmidae cercariae.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the molecular data of the ITS2 rDNA region, Echinochasmus sp. 2, obtained experimentally by Molnár et al (2016), entered the second cluster together with Stephanoprora. Mature worms of this species, like other echinochasmids in the cluster, had 20 adoral spines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations